Political Elites and Their Role in the Formation of Civil Society in Ukraine - Назарчук, Олександр Миколайович (Київський національний університет імені Тараса Шевченка, 2024)
The article explores the key role of political elites in shaping civil society in Ukraine. It analyzes the impact of political elites on the development of democratic institutions, their ability to engage in institutional interaction with civil organizations, and their participation in ensuring democratic transformations. It is established that political elites act as key agents determining the direction of political transformations. However, their influence is often accompanied by challenges such as corporate interests, corrupt practices, and limited transparency in decision-making processes. The stages of the development of political elites since Ukraine’s independence are examined. In the early stages, they consisted of former post-Soviet cadres, which slowed the democratization process. After the Orange Revolution, and especially following the 2014 Revolution of Dignity, the political elite underwent a renewal, contributing to greater transparency and openness in decision-making. The study reveals that the influence of oligarchic structures remains a significant factor that complicates the implementation of reforms. The role of public consultations and open meetings with the public in the democratization of political processes is analyzed. It is found that these mechanisms are important for engaging citizens in key political decision-making, but their effectiveness is often limited by the internal pressure of political elites’ interests. The research concludes that sustainable democratic development requires further improvement of mechanisms for citizen participation in the political process, increased transparency and accountability of the government, and enhanced public oversight of political elites. It is suggested that digital platforms be more actively only expand opportunities for citizen participation in political life but also provide timely feedback between the authorities and civil society. It is identified that such platforms could serve as effective tools for improving transparency in decisionmaking processes, promoting the openness of political elites, and strengthening public control over their activities. It is argued that achieving sustainable democratic development necessitates balancing the interests of political elites and civil society by creating inclusive mechanisms for discussion and decision-making. The article concludes that future research should focus on examining specific mechanisms of interaction between political elites and civil society and analyzing their effectiveness during political crises.

У статті досліджено ключову роль політичних еліт у формуванні громадянського суспільства в Україні. Проаналізовано вплив політичних еліт на розвиток демократичних інститутів, їхню здатність до інституційної взаємодії з громадськими організаціями та участь у забезпеченні демократичних перетворень. Встановлено, що політичні еліти виступають як ключові суб’єкти, що визначають вектор політичних трансформацій. Однак їхній вплив часто супроводжується викликами, такими як корпоративні інтереси, корупційні практики та обмежена прозорість у прийнятті рішень.Досліджено етапи розвитку політичних еліт з моменту незалежності України. На початкових етапах вони складалися з колишніх пострадянських кадрів, що сповільнювало процес демократизації. Після Помаранчевої революції та особливо після Революції Гідності 2014 року відбулося оновлення політичної еліти, що сприяло більшій прозорості і відкритості в прийнятті рішень. Виявлено, що вплив олігархічних структур залишається значним фактором, який ускладнює проведення реформ. Проаналізовано роль публічних консультацій та відкритих зустрічей з громадськістю у демократизації політичних процесів. Встановлено, що ці механізми є важливими для залучення громадян до ухвалення ключових політичних рішень, проте їхня ефективність часто обмежена через внутрішній тиск інтересів політичних еліт. Узагальнено, що для підтримки сталого демократичного розвитку необхідно подальше вдосконалення механізмів залучення громадян до політичного процесу, збільшення прозорості та відповідальності влади, а та- кож посилення контролю за діяльністю політичних еліт з боку громадськості.Пропонується активіше використовувати цифрові платформи для взаємодії між владою та громадськістю, що дозволить не тільки розширити можливості для участі громадян у політичному житті, але й забезпечити оперативний зворотний зв’язок між владою та громадянським суспільством. Виявлено, що такі платформи можуть стати дієвим інструментом для покращення прозорості процесів ухвалення рішень, сприяти відкритості політичних еліт та посилити контроль громадськості за їхньою діяльністю.Обґрунтовано, що для досягнення стійкого демократичного розвитку необхідно збалансувати інтереси політичних еліт та громадянського суспільства, створюючи інклюзивні механізми для обговорення та ухвалення рішень. Узагальнено, що ключовими напрямами подальших досліджень має стати вивчення конкретних механізмів взаємодії між політичними елітами та громадянським суспільством, а також аналіз їхньої ефективності в умовах політичних криз.
Політичні еліти та їхня роль у формуванні громадянського суспільства в Україні
Keywords: social responsibility; political leadership; institutional development; democratic processes; civic engagement; political elites; соціальна відповідальність; політичне лідерство; інституційний розвиток; демократичні процеси; громадська участь; політичні еліти